Toxicological effects of copper on bioaccumulation and mRNA expression of antioxidant, immune, and apoptosis-related genes in Chinese striped-necked turtle (Mauremys sinensis) - Ali, Zeeshan; Khan, Ijaz; Iqbal, Muhammad Shahid; Zhang, Qiongyu; Ai, Xiaoqi; Shi, Haitao; Ding, Li; Hong, Meiling (Frontiers in Physiology, 2023)
Heavy metals are among the most ubiquitous environmental pollutants of recent decades. Copper is commonly used to control algal blooms or macrophyte and waste infestations, its ambient concentration has increased significantly, indicating possible environmental risk. To investigate the effects of copper exposure on bioaccumulation, antioxidant defense, immune response, and apoptosis in the Chinese Striped-necked Turtle Mauremys sinensis, three experimental groups, control (0.0mg/l), Cu2 (2mg/l) and Cu4 (4mg/l) were designed, and sampled at 14 and 28 days.Results showed that copper accumulates in different organs depending on the concentration and exposure time, Liver > Kidney > Gut > Heart > Brain > Muscle and the time order was 28 days > 14 days. The liver enzymes AST, ALT, and ALP decreased when the turtles were exposed to copper stress, while the contents of bilirubin TBIL, DBIL, IBIL, and LDH showed a significant upward trend. Similarly, the mRNA expression level of acetylcholinesterase AChE in the brain was significantly downregulated upon copper exposure. An upward trend was noticed in the liver Metallothionein MT mRNA expression levels compared to the control group. The mRNA expression levels of antioxidant enzymes CAT, SOD, MnSOD, and GSH-PX1 in the liver increased initially and then significantly decreased. Furthermore, the relative mRNA expression levels of inflammatory cytokines IL-1β, IL-8, TNF-α, and IFN-γ involved in inflammatory response significantly upregulated. Copper significantly increased the hepatic mRNA transcription of heat shock proteins HSP70 and HSP90 at different exposure durations. In addition, the relative mRNA levels of caspase3, caspase8, and caspase9 related to the caspase-dependent apoptotic pathway significantly increased under copper stress. These results explain that copper toxicity causes bioaccumulation, promotes oxidative stress, obstructs immunity, and induces inflammation and apoptosis by altering their gene expression levels in Mauremys sinensis.